A pooled mean group analysis on aid and growth - Tan, K (2006)
This paper uses the pooled mean group estimator and an extended annual dataset to examine the effectiveness of aid on growth. The results indicate a signifi…cant long-run impact of aid on growth, but conditioning aid on 'good' policy reduces the long-run growth rate.